A study on problem faced by pregnant women - E, Arachselvi (International Journal of Psychosocial Rehabilitation, 2020)
This Study is all about the problems faced by pregnant women. The main aim of the study is to create awareness about pregnant women. Descriptive research helps to portray accurately the characteristics of particular individual, situation or group. Convenience sampling method is used in this study to collect the samples. When population elements are selected for inclusion in the sample based on access is called convenience sampling. The statistical tool used is percentage analysis, which includes Independent sample t test, Chi-square, Correlation and ANOVA. The total number of responses collected in the survey is around 1638 .It was found that constitution makes it mandatory for the Government to protect and promote freedom, and to assure every citizen a decent standard of living. In this study I have concluded that a significant proportion of pregnancies are complicated by serious medical illness requiring treatment. Regardless of a worldwide requirement for the utilization of drug during pregnancy, the medicinal research network needs rigorous proof for security and adequacy of medications and preventives frequently taken by pregnant ladies. Given the organic contrasts between pregnant ladies and the remainder of the populace, the need to assemble information on the manner by which meds act in the pregnant body is basic to the wellbeing of pregnant ladies and their posterity.